Calcification and ossification in conventional schwannoma: A clinicopathologic study of 32 cases. Issue 2 (3rd December 2019) - Din, Nasir U.; Fritchie, Karen; Tariq, Muhammad U.; Ahmed, Arsalan; Ahmad, Zubair
Abstract : Calcification and ossification are uncommon in schwannomas; however, when present these findings may cause diagnostic confusion with other mesenchymal tumors which more frequently harbor these features. We sought to better characterize the type and rate of calcification and ossification in schwannomas. Cases of schwannoma diagnosed at our institution from 2005 to 2019 were reviewed to determine the type and amount of calcification and ossification present. Of 2116 total cases of schwannoma reported during the study period, 38 cases harbored calcification or ossification per the pathology report. Thirty‐two of the 38 cases had slides available for review, of which 27 (84.3%) showed calcification, nine showed ossification (28.1%), and four (12.5%) cases demonstrated both. Foci of ossification typically occurred adjacent to large vessels. Of the 27 cases showing calcification, coarse dystrophic calcification was seen in 22 cases, psammomatous calcification in nine cases, and combined dystrophic and psammomatous calcification was seen in four cases. Cases with psammomatous calcification predominantly occurred in spinal roots and cerebellopontine angle of a younger age group with almost equal gender distribution. All four cases tested for protein kinase cyclic adenosine monophosphate‐dependent type I regulatory subunit alpha immunohistochemical stain demonstrated retained expression. We confirm that calcification and ossification are rare findings in schwannoma. Awareness that these features may be present in these tumors will prevent misdiagnosis and ensure appropriate clinical management.